Effect of graphene oxide dosage on the thermal and rheological behavior of asphalt for tropical road conditions - Mendoza, Erick; Tene, Talia; Albuja-Sánchez, Jorge; Cuenca, Guisella; Ramón, John; Anzules, David; Vacacela Gomez, Cristian; Cruz Salazar, Yolenny; Caputi, Lorenzo S.; Straface, Salvatore (Frontiers in Chemistry, 2025)
This study investigates graphene oxide (GO) as a low-percent modifier for AC-30 asphalt used in tropical conditions. GO was added at 0.2, 0.4, and 0.6 wt% and tested through standard binder tests and RTFO short-term aging. Unaged binders with GO showed increased viscosity and hardness—viscosity rose by up to approximately 26%, penetration decreased by about 8%–13%, and the softening point rose slightly—indicating a stiffer initial matrix. During mixing at 135 °C–165 °C, both rotational and kinematic viscosities increased, with the highest gains near 0.4 wt%, suggesting a non-linear response to dosage. Under RTFO aging, GO-modified binders exhibited a higher viscosity aging index than the unmodified AC-30, indicating that GO enhances initial stiffness and does not compromise short-term oxidative hardening. Flash and fire points did not show systematic reductions at these dosages. Overall, sub-percent GO improves high-temperature rheology relevant for hot-climate pavements, but there is a trade-off between better early rutting resistance and potential stiffening with aging. Future research will include PAV/DSR testing and analysis of dispersion better to understand long-term behavior and processing at the plant level.